THE INFLUENCE OF PERCEPTION OF EASY AND PERCEPTION OF BENEFIT ON INTENTION TO USE FINANCIAL TECHNOLOGY AS A TOOL OF PAYMENT AMONG STUDENTS IN THE CITY OF JEMBER - Ferdiansyah, Moch Farhan; Hafidzi, Achmad Hasan; Umamy, Septy Holisa (Universitas Muhammadiyah Tangerang, 2024)
Technology will continue to evolve to meet all human needs, which always require faster mobility than what is seen today. Startup businesses are developing financial technology to meet the demand for a profitable and convenient payment system. The purpose of this study is to determine and explore how perceived benefits and convenience can influence students' intention to use financial technology as a payment method in Jember City. This study used a proportional random sampling process and a quantitative approach with a sample size of 400 students in Jember City. In this study, a questionnaire was used as a data collection tool. The survey was distributed offline and online using Google Forms links to measure the impact of each variable. A statistical program called SPSS 21 was used to conduct multiple linear regression analysis in this study. The findings show that the propensity to use financial technology as a payment method is influenced, both simultaneously and partially, by perceived benefits and convenience.